(3OQGSGJ fXQjI h JWHjbjIs - (3eMeO YHO GdYRjR(B, (3YLejIs; (3fGUa GjeGf YWjI(B;(3fLG Ydj YHO GdhgGH(B, s ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYI ddfTQ(B,s, 2006)
(3eaghe hNUGFU GdJNJa (B-(3NUGFU GdJNda(B--(3ebGjjS Gdfeh GdGbJUGOj(B-(3fXQjGJ hGSJQGJLjI GdJfejI GdGbJUGOjI(B--(3Jehjd GdJfejI GdGbJUGOjIGdTQcGJ eJYOOI GdLfSjGJ GdGUdGM GdGbJUGOj aj eUQ(B-(3feGPL GdGeJMGfGJs
Keywords: (3GdJfejI GdGbJUGOjIs; (3GdSjGSI GdGbJUGOjIs; (3Gdfeh GdGbJUGOjs